2022
DOI: 10.1111/nph.18361
|View full text |Cite
|
Sign up to set email alerts
|

The ecological implications of intra‐ and inter‐species variation in phenological sensitivity

Abstract: Plant-pollinator mutualisms rely upon the synchrony of interacting taxa. Climate change can disrupt this synchrony as phenological responses to climate vary within and across species. However, intra-and interspecific variation in phenological responses is seldom considered simultaneously, limiting our understanding of climate change impacts on interactions among taxa across their ranges.We investigated how variation in phenological sensitivity to climate can alter ecological interactions simultaneously within … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 123 publications
0
14
0
Order By: Relevance
“…Both our results and others (e.g. Li et al ., 2019) suggest that urbanization advances plant phenology in colder regions where plants tend to be less phenologically sensitive to temperature (Menzel et al ., 2006; Sherry et al ., 2007; Wolkovich et al ., 2012; Park et al ., 2019; Love & Mazer, 2021; Xie et al ., 2022). This suggests that: urbanization‐driven phenological shifts are not only a result of increases in temperature; and urbanization affects long‐term temperature more so than it does the degree of inter‐annual variation in temperature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both our results and others (e.g. Li et al ., 2019) suggest that urbanization advances plant phenology in colder regions where plants tend to be less phenologically sensitive to temperature (Menzel et al ., 2006; Sherry et al ., 2007; Wolkovich et al ., 2012; Park et al ., 2019; Love & Mazer, 2021; Xie et al ., 2022). This suggests that: urbanization‐driven phenological shifts are not only a result of increases in temperature; and urbanization affects long‐term temperature more so than it does the degree of inter‐annual variation in temperature.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, advanced plant flowering and leaf out, and delayed leaf senescence were associated with higher human population density in colder areas, but these effects were reversed in warmer areas (Li et al ., 2019, 2021). Interestingly, studies examining the effect of temperature on plant phenology have often found the opposite pattern – increases in temperature generally advanced phenology to greater degrees in warmer areas (Menzel et al ., 2006; Sherry et al ., 2007; Wolkovich et al ., 2012; Love & Mazer, 2021; Xie et al ., 2022). This suggests that urbanization‐driven plant phenological shifts are not simply because of local increases in temperature (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…The phenological timing of species and their responses to climate have been demonstrated to vary substantially across latitude, both within and among species (Park et al, 2019; Park, Newman, et al, 2021; Xie et al, 2022). Although these studies focused on temperate floras, we expect similar responses exist in the tropics, as the ranges of numerous taxa span multiple tropical biomes (Lucresia et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, we examined the effects of mean annual temperature and the precipitation of the warmest quarter on phenological similarity among native and non‐native species across bioregions. As it has been demonstrated that the effect of temperature on phylogenetic and phenological patterns can be mediated by precipitation, we also included interaction terms between temperature and precipitation variables (Park et al., 2020; Park, Xie, et al., 2023; Xie et al., 2022). Invasive status was included as a fixed effect.…”
Section: Methodsmentioning
confidence: 99%
“…This mirrors the findings of It is possible that these patterns may differ at finer spatial and temporal scales. The timing of phenological events can be influenced by local biotic and abiotic conditions (Jackson, 1966;Vitasse et al, 2021;Ward et al, 2018) and thus vary across species ranges (Park et al, , 2022Xie et al, 2022Xie et al, , 2023. The coarse nature of our species-level phenological estimates does not account for such local variation.…”
Section: Close Relatives Make Bad Neighboursmentioning
confidence: 99%